Compensatory neuritogenesis of serotonergic afferents within the striatum of a transgenic rat model of Parkinson's disease - Stemick, Judith; Gauer, Carina; Wihan, Jeanette; Moceri, Sandra; Xiang, Wei; von Hörsten, Stephan; Kohl, Zacharias; Winkler, Jürgen (Brain Research, 2020)
The majority of patients with Parkinson's disease (PD) suffer from L-DOPA-induced dyskinesia (LID). Besides a dysfunctional dopaminergic system, changes of the serotonergic network may be linked to this severe and adverse symptom. Particularly, serotonergic neurons have the potential to synthesize dopamine, likely associated with a disproportional dopamine release within the striatum. We hypothesized that the serotonergic system is adaptively altered in the striatum due to the reduced dopaminergic input. To answer this question, we analyzed a transgenic rat PD model ubiquitously expressing human α-synuclein using a bacterial artificial chromosome. Neurite analysis showed a profound loss of dopaminergic fibers by 30–40% within the dorsal striatum paralleled by a 50% reduction of dopaminergic neurons in the substantia nigra pars compacta. In contrast, serotonergic fibers showed an increased fiber density in the dorsal striatum by 100%, while the number of serotonergic neurons within the raphe nuclei (RN) and its proximal neuritic processes were unaffected. Furthermore, both the dopaminergic and serotonergic fiber density remained unchanged in the neighboring motor cortex M1/M2. Interestingly, essential enzymes required for L-DOPA turnover and dopamine release were expressed in serotonergic neurons of the RN. In parallel, the serotonergic autoreceptor levels involved in a serotonergic negative feedback loop were reduced within the striatum, suggesting a dysfunctional neurotransmitter release. Overall, the increased serotonergic fiber density with its capacity for dopamine release within the striatum suggests a compensatory, site-specific serotonergic neuritogenesis. This maladaptive serotonergic plasticity may be linked to adverse symptoms such as LIDs in PD.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Dopamine; L-DOPA-induced dyskinesia; Parkinson's disease; Serotonin; Striatum; α-synuclein

CSF1R-mediated myeloid cell depletion shifts the ratio of motor cortical excitatory to inhibitory neurons in a multiple system atrophy model - Gauer, Carina; Battis, Kristina; Schneider, Yanni; Florio, J. B.; Mante, M.; Kim, H. Y.; Rissman, R. A.; Hoffmann, Alana; Winkler, Jürgen (Experimental Neurology, 2024)
Motor cortical circuit functions depend on the coordinated fine-tuning of two functionally diverse neuronal populations: glutamatergic pyramidal neurons providing synaptic excitation and GABAergic interneurons adjusting the response of pyramidal neurons through synaptic inhibition. Microglia are brain resident macrophages which dynamically refine cortical circuits by monitoring perineuronal extracellular matrix and remodelling synapses. Previously, we showed that colony-stimulating factor 1 receptor (CSF1R)-mediated myeloid cell depletion extended the lifespan, but impaired motor functions of MBP29 mice, a mouse model for multiple system atrophy. In order to better understand the mechanisms underlying these motor deficits we characterized the microglial involvement in the cortical balance of GABAergic interneurons and glutamatergic pyramidal neurons in 4-months-old MBP29 mice following CSF1R inhibition for 12 weeks. Lack of myeloid cells resulted in a decreased number of COUP TF1 interacting protein 2-positive (CTIP2+) layer V pyramidal neurons, however in a proportional increase of calretinin-positive GABAergic interneurons in MBP29 mice. While myeloid cell depletion did not alter the expression of important presynaptic and postsynaptic proteins, the loss of cortical perineuronal net area was attenuated by CSF1R inhibition in MBP29 mice. These cortical changes may restrict synaptic plasticity and potentially modify parvalbumin-positive perisomatic input. Collectively, this study suggests, that the lack of myeloid cells shifts the neuronal balance toward an increased inhibitory connectivity in the motor cortex of MBP29 mice thereby potentially deteriorating motor functions.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Colony-stimulating factor 1 receptor; Excitation-inhibition balance; GABAergic interneurons; Microglia-neuron-interaction; Motor cortex; Multiple system atrophy; PLX5622; Pyramidal neurons

Distinct forebrain regions define a dichotomous astrocytic profile in multiple system atrophy - Schneider, Yanni; Gauer, Carina; Andert, Marie; Hoffmann, Alana; Riemenschneider, M. J.; Krebs, W.; Chalmers, Nicholas; Lötzsch, C.; Naumann, Ulrike; Xiang, Wei; Rothhammer, Veit; Beckervordersandforth, Ruth; et al. (Acta Neuropathologica Communications, 2024)
The growing recognition of a dichotomous role of astrocytes in neurodegenerative processes has heightened the need for unraveling distinct astrocytic subtypes in neurological disorders. In multiple system atrophy (MSA), a rare, rapidly progressing atypical Parkinsonian disease characterized by increased astrocyte reactivity. However the specific contribution of astrocyte subtypes to neuropathology remains elusive. Hence, we first set out to profile glial fibrillary acidic protein levels in astrocytes across the human post mortem motor cortex, putamen, and substantia nigra of MSA patients and observed an overall profound astrocytic response. Matching the post mortem human findings, a similar astrocytic phenotype was present in a transgenic MSA mouse model. Notably, MSA mice exhibited a decreased expression of the glutamate transporter 1 and glutamate aspartate transporter in the basal ganglia, but not the motor cortex. We developed an optimized astrocyte isolation protocol based on magnetic-activated cell sorting via ATPase Na+/K+ transporting subunit beta 2 and profiled the transcriptomic landscape of striatal and cortical astrocytes in transgenic MSA mice. The gene expression profile of astrocytes in the motor cortex displayed an anti-inflammatory signature with increased oligodendroglial and pro-myelinogenic expression pattern. In contrast, striatal astrocytes were defined by elevated pro-inflammatory transcripts accompanied by dysregulated genes involved in homeostatic functions for lipid and calcium metabolism. These findings provide new insights into a region-dependent, dichotomous astrocytic response—potentially beneficial in the cortex and harmful in the striatum—in MSA suggesting a differential role of astrocytes in MSA-related neurodegenerative processes.
CRIS-Team Scopus Importer:2024-01-12